1980
DOI: 10.1115/1.3149584
|View full text |Cite
|
Sign up to set email alerts
|

Fiber Optic Microfluorimetry for Acute and Chronic In-Vivo Animal Studies

Abstract: Highly localized long-term measurements of tumor transport properties are performed with pairs of adjacent, parallel single-strand optic fibers embedded in a laboratory animal. External illumination and light sensing equipment detect local concentration of a fluorescent indicator initially injected into the venous system. Under appropriate conditions, blood flow per unit volume, capillary permeability, and uptake of fluorescent drugs can be determined from the fluorescence time history. The observation volume … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1984
1984
1999
1999

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…A preferential distribution of ALA‐derived porphyrins in tumor cells provides the possibility of in situ detection of the porphyrin fluorescence in the superficial transformed epithelial cells of the skin and internal hollow organs by means of fiberoptic point monitoring systems or of fluorescence imaging systems 220, 221. Such a procedure can be performed noninvasively in vivo with immediate results and can also be used for pharmacokinetic studies 83, 220‐223. Topical and local internal administration of ALA may be used for such diagnostic purposes because intravesical, intrauterine, and inhalant administrations do not produce generalized cutaneous photosensitivity.…”
Section: Major Current Challengesmentioning
confidence: 99%
“…A preferential distribution of ALA‐derived porphyrins in tumor cells provides the possibility of in situ detection of the porphyrin fluorescence in the superficial transformed epithelial cells of the skin and internal hollow organs by means of fiberoptic point monitoring systems or of fluorescence imaging systems 220, 221. Such a procedure can be performed noninvasively in vivo with immediate results and can also be used for pharmacokinetic studies 83, 220‐223. Topical and local internal administration of ALA may be used for such diagnostic purposes because intravesical, intrauterine, and inhalant administrations do not produce generalized cutaneous photosensitivity.…”
Section: Major Current Challengesmentioning
confidence: 99%
“…Goldstein et a2. [33] have developed a fiber optic microfluorimetric technique for measurement of blood clearance and tissue uptake response characteristics of fluorescein conjugates in tumors. The uncertainties associated with hemoglobin absorption effects have important consequences, in light of the present findings, as fiber optic techniques are not amenable to plasma layer monitoring.…”
Section: / Platementioning
confidence: 99%
“…8 The use of fiber optics have shown promise of measuring in situ transport. For example, Goldstein et al 9 have demonstrated that multiple fiber optic probes can be used in the investigation of solute transport of a fluorescence dye in tissues by implantation. Yet, to obtain reasonable spatial resolution they found the need to use an array of individual sensors and then combine the responses of each sensor to generate a transport map.…”
Section: Introductionmentioning
confidence: 99%